The use of critical velocity in swimming. A place for critical stroke rate. - Dekerle, J. (2006)
For any swimmer, a hyperbolic relationship links velocity (v) and stroke rate (SR) to time to exhaustion (t). The asymptotes of these relationships are called Critical Velocity (CV) and Critical Stroke Rate (CSR). Both could be maintained, at least in theory, indefinitely. This review presents the origins of these two concepts, their physiological / biomechanical underpinnings to emphasis their usefulness for training. Coaches should appreciate the ease in using the CV model to set training loads, monitor training effects, and predict performance. The CSR concept is very recent and should be further investigated. However, current available knowledge suggests there is merit in using the two parameters for training.